Chaotic photon orbits and shadows of a non-Kerr object described by the Hartle–Thorne spacetime. (7th July 2022) - Kostaros, K; Pappas, G
Abstract: The data from the event horizon telescope have provided a novel view of the vicinity of the horizon of a black hole (BH), by imaging the region around the light-ring. They have also raised hopes for measuring in the near future, features of the image (or the shadow) related to higher order effects of photons travelling in these regions, such as the appearance of higher order bright rings produced by more than one windings of photons around the light-ring. While the prospect of measuring these fine features of Kerr BHs is very interesting in itself, there are some even more intriguing prospects for observing novel features of possible non-Kerr objects, in the case that the subjects of our images are not the BH solutions of general relativity. In the hope of sufficient resolution being available in the future, we explore in this work the structure and properties of null geodesics around a Hartle–Thorne (HT) spacetime that includes a deformation from the Kerr spacetime characterised by the quadrupole deformation δq . These spacetimes have been found to exhibit a bifurcation of the equatorial light-ring to two off-equatorial light-rings in a range of δq s and spin parameters. In addition to this, there is a range of parameters where both the equatorial and the off-equatorial light-rings are present. This results in the formation of a pocket that can trap photon orbits. We investigate the properties of these trapped orbits and find that chaotic behaviour emerges. Some of these chaotic orbits are additionally found to be 'sticky' and get trapped close to periodic orbits for long times. We also explore how these novel features affect the shadow and find that the off-equatorial light-rings produce distinctive features that deform its circular shape, while the chaotic behaviour associated to the pocket creates features with fractal structure. These results are shown to be quite general, extending to higher order HT spacetimes.